Glow - Kennedy, Raven (Kennedy, Raven. Plated prisoner series, 2024)
Despite the dark threat of the Slade Ravinger, the other monarchs are still gunning for Midas who vows to rise from the ashes and wield his power like a phoenix in the fourth novel of the series following Gleam.